Bernard Shaw and Gabriel Pascal - Shaw, Bernard 1856-1950; Pascal, Gabriel 1894-1954 (Shaw, George B.: [Selected correspondence], 1996)
The letters reveal the great extent to which Pascal, unlike his predecessors, scrupulously kept Shaw informed of what he did. We learn about whom Pascal negotiated with, the merits of association with certain individuals or businesses, contract problems, the backbiting and backstabbing of the industry, difficulties with casting, and progress throughout the filming. Shaw accepted and embellished some of Pascal's ideas for production, and vehemently disagreed with others. Their correspondence highlights the differences in personality between the two men. Shaw was ever the astute businessman, while Pascal was the eager artist. Shaw the methodical mastermind contrasted sharply with Pascal the entrepreneur with many projects under development, few of which came to fruition